Sekolah Penggerak Program: An Analysis of Implementation in Junior High Schools - Sururi; Afifah, Dea Elisa; Kurniatun, Taufani Chusnul; Hafidh, Zaini (Universitas Pendidikan Ganesha, 2023)
This research is based on the Merdeka Belajar policy regarding the Sekolah penggerak Program. This study aims to analyze the implementation of this policy in Junior High Schools through Edward III's theory of public policy implementation, which consists of four aspects, namely communication, resources, disposition, and bureaucratic structures that play a role in the implementation of the policy. The research method used in this research uses a descriptive-qualitative approach and uses data collection techniques, namely interviews and documentation studies. Researchers use software to help facilitate data and information processing, thus helping facilitate data and information management. The results of this research indicate that the implementation of the Sekolah Penggerak program policy at Junior High Schools has met the aspects of communication, resources, disposition, and bureaucratic structure well, even though in the first year the Sekolah penggerak Program experienced many obstacles in its implementation. In the second and third years, The implementation of the three Sekolah Penggerak programs is running more smoothly. The aspect that needs to be improved is the resource aspect, especially budget resources.